Effect of VG Model Parameter Changes on Soil Infiltration Under Varying-head Infiltration - LI Xinli; CHEN Li (Renmin Zhujiang)
In order to explore the influence of various parameters of Van Genuchten model on infiltration characteristics of soils of different textures in the condition of varying-head infiltration,based on the HYDRUS-1D model,this paper analyzes the sensitivity of VG model parameters under different soil texture and output variables by the partial analysis method.The results show that:The influence of each parameter on the pressure head decreases as the soil texture becomes finer,and the parameter sensitivity of soils with same texture reaches the maximum at the end of the rainfall,and then decreases with the increase of time;The effects of positive and negative perturbation of the same parameter on cumulative infiltration are basically the same;n、Ks、θs have greater influence on pressure head and cumulative infiltration;The influence of VG model parameters on the wetting front transport distance for soil of different textures varies greatly,and the sensitivity of each parameter is ranked as follows:θs＞Ks＞α＞n＞θr(sandy loam),α＞θs＞Ks＞θr＞n(loam),n＞α＞θr＞θs＞Ks(clay loam).Boundary conditions are one of the important factors affecting parameter sensitivity of VG model.Therefore,when applying the model,more attention should be paid to the choice of boundary conditions and the accuracy of the parameters θs、α、n、Ks.